Analysis of pipe material classification using the MUSIC-3D method in the oil and gas industry - Winoto, Erwin Shafira; Qisthani, Nabila Noor (Journal Industrial Servicess, 2025)
The oil and gas industry plays a crucial role in meeting global energy needs, significantly impacting sectors like energy, manufacturing, and transportation. Managing material inventory effectively is vital to keeping production processes running smoothly. Pipes, which are essential for transporting fluids and gases, come into various materials, sizes, and specifications, making accurate classification a must. To prioritize material needs efficiently, a thorough classification based on historical usage data is essential. This study explores how to set material priorities and develop inventory control policies using the MUSIC-3D method, which combines ABC, SDE, and FSN analyses. Our findings show that 45 materials fall into the very high-priority category, 91 are moderately high priority, and just 1 is low priority. These classifications help shape inventory policies by evaluating material criticality, procurement lead times, and usage rates. We suggest adjusting parameters like Economic Order Quantity (EOQ), Safety Stock (SS), Reorder Point (ROP), and ordering schedules to balance material availability with cost efficiency. This approach ensures that critical materials are always on hand while keeping storage costs and procurement risks to a minimum.